Pengembangan Multimedia Pembelajaran Sejarah Berbasis Chronological Thinking untuk Siswa SMA - Yeni Puspita Sari; Ofianto Ofianto; Ridho Bayu Yefterson (Jurnal Halaqah, 2019)
This research aims to develop a historical video based on multimedia for senior high school. The research produced a product that is a historical video based on multimedia, which is in accordance with the chronology of historical events that are feasible and practical. The type of research is development research using the 4D model, consisting of several stages, The first stages are Define, by observation in SMAN 7 Padang, Design phase by designing media and compiling validation and practicality questionnaire instruments, Develop stages by developing media using videoscribe and movie maker applications. Then, do media validation by the expert lecturer and product trials by history teachers. The test subject of this research is 32 students of grade XI MIPA 3 of SMAN 7 Padang. The result of this research produced a product such a historical video learning based on multimedia. The result of product feasibility conducted by 2 expert lecturers, whereas a product test conducted by 2 historical teachers and 32 students grade XI MIPA 3. The media declared very feasible through the assessment of media experts after being tested and implemented in learning and tested for practicality by students and teachers, the media was very practical to be used as a learning media.